Pemberdayaan Lansia dalam Perekonomian di Masa Pandemi Di Kelurahan Sidodadi - Anjani, Yuli Safitri; Nur, Hamdan (Yayasan Mandar Indonesia, 2022)
During this pandemic, many Indonesians have lost their jobs as a result of layoffs and various other factors, this greatly impacts on the welfare of life, especially for the elderly, most of whom may no longer work and depend on young productive ages to live. Elderly is someone aged 60 years and over. Along with increasing age, the elderly will experience changes such as decline and decline in physical function. With the problems faced by the elderly, it is necessary to have a caring attitude from the government, society, and the elderly themselves. This pandemic has a multidimensional impact on various aspects of life, with policies to stay at home, and other measures restricting movement, disruption of social relations, and reduced access to various services, which can exacerbate the risk of economic income, especially for the elderly. Meanwhile, the proportion of the elderly population (elderly) from 1980 to 2020 continues to increase. Age 60 years and over is the final stage of the aging process which has an impact on three aspects, namely biological, economic, and social. Biologically, the elderly will experience a continuous aging process which is marked by a decrease in physical endurance and is susceptible to disease. Elderly empowerment is every effort to improve physical, mental, spiritual, social, knowledge and skills abilities so that the elderly are ready to be empowered according to their respective abilities.